The Eco- tourism Management through the Community based participation on Sa-rai Islands, Satun Province /การจัดการท่องเที่ยวเชิงนิเวศโดยกระบวนการมีส่วนร่วมของชุมชนในพื้นที่เกาะสาหร่าย จังหวัดสตูล - สุจิตราภรณ์ จุสปาโล, Sujitraporn Jussapalo / (Journal of Community Development Research (Humanities and Social Sciences); Vol 6 No 1 (2556): January - June 2013, 2014)
การวิจัยครั้งนี้ มีวัตถุประสงค์เพื่อสร้างโปรแกรมการท่องเที่ยวเชิงนิเวศและรูปแบบการจัดการท่องเที่ยวเชิงนิเวศโดยกระบวนการมีส่วนร่วมของชุมชนเกาะสาหร่าย จังหวัดสตูล โดยใช้วิธีการศึกษาข้อมูลปฐมภูมิได้จากการสัมภาษณ์ การสนทนากลุ่ม การประชุมระดมความคิดเห็นจากเจ้าหน้าที่องค์การบริหารส่วนตาบล ผู้นาชุมชน และประชาชนในท้องถิ่น ข้อมูล ทุติยภูมิจากเอกสารต่างๆ ผลการศึกษา พบว่า โปรแกรมการท่องเที่ยวสาเร็จรูปที่เหมาะสมกับชุมชน เพื่อการเรียนรู้วิถีชีวิตความพอเพียงของชาวบ้าน ร่วมกิจกรรมรักษ์โลกรักษ์สิ่งแวดล้อม เช่น เดินชมปะการัง สัมผัสสัตว์หลากหลายชนิด การเลี้ยงสาหร่ายผมนาง ปลูกหญ้าทะเลอาหารพะยูน ปล่อยพันธุ์ปูม้าไข่ สร้างบ้านปลาการ์ตูน ปลูกปะการังเขากวาง เป็นต้น และ พักโฮมสเตย์ชุมชน ระยะเวลา 2 วัน 1 คืน และรูปแบบการจัดการท่องเที่ยวเชิงนิเวศโดยได้กาหนดโครงสร้างการบริหารและบทบาทหน้าที่ของคณะกรรมการฝ่ายต่างๆ เพื่อเอื้อต่อการจัดการท่องเที่ยวของชุมชน และสร้างรายได้จากอาชีพเสริม เรื่องการท่องเที่ยว โดยนาร่องที่ชุมชนบ้านบากันใหญ่ หมู่ที่ 2 ตาบลเกาะสาหร่าย จังหวัดสตูล คำสำคัญ: การท่องเที่ยวเชิงนิเวศ เกาะสาหร่าย จังหวัดสตูล กระบวนการมีส่วนร่วมของชุมชน โปรแกรมการท่องเที่ยวเชิงนิเวศ The study aims to create the eco-tourism package and the models of eco-tourism management through the community based participation on Sa-rai Island, Satun Province. The primary sources of data were collected from interviews, focus groups, brainstorming of local administrators, local leaders, and local people while the secondary ones were gathered from documents. It was revealed that the appropriate model of eco-tourism management should integrate the learning of sufficiency living styles of the locals, staying at local home stay for 2 days and one night and activities involving world and environment saving such as experiencing corals and a variety of animals, culturing Phom Nang algae, growing sea grass for dugongs, freeing blue crabs, creating habitats for coral fish. The model of eco-tourism management also determines the structure of administration and roles of committees to facilitate the tourism of the community and to create extra incomes for the locals. This model was pioneered at Ban Ba Gun Moo 2, Sa-rai Island, Satun. Keywords: Eco-Tourism, Sa-rai Islands, Satun, Community based participation, Eco-Tourism package
Keywords: การท่องเที่ยวเชิงนิเวศ เกาะสาหร่าย จังหวัดสตูล กระบวนการมีส่วนร่วมของชุมชน โปรแกรมการท่องเที่ยวเชิงนิเวศ Eco-Tourism, Sa-rai Islands, Satun, Community based participation, Eco-Tourism package